Quality Assessment of Visual Landscape for Sustainable Tourism in Bogor, Puncak Cianjur, West Java, Indonesia - Krisantia, Ina; Intan Mangunsong, Nur; Hakim, Rustam; Bagus Rabindra, Ida (International Journal of Engineering and Technology, 2019)
Visual scenery of an area is very important in the destination of a tourist destination. In Indonesia there are many tourist areas that experience an increase in visual appeal because of the faster construction.The purpose is to identify and to quanti- fyÂ quality ofÂ visual landscape in the tourist area of Bogor, Puncak Cianjur. MethodÂ was used Visual Resources Assess- ment Procedure (VRAP).Â Visual quality wereÂ the sum of visual elements water, vegetation, land surface, user activity andÂ other con- siderations. The results obtained were Cisarua subdistrict has a high visual qualityÂ while Cibodas Botanical GardenÂ has the highest value in tourist destinations. These results can contribute to the sustainable tourism through visual managementclass such as class II for Retentention areas in Cisarua district and Cipanas district, class III for partial retention areas in Megamendung district and class IV for modify areas in Ciawi and Pacet district. Â Â